The role of fish intake on asthma in children: A meta‐analysis of observational studies. Issue 4 (June 2018) - Papamichael, M. M.; Shrestha, S. K.; Itsiopoulos, C.; Erbas, B.
Abstract: Background: The evidence is mixed on the use of long chain Omega‐3 fatty acids in the prevention and management of childhood asthma. Methods: We conducted a systematic search and meta‐analysis investigating the role of fish intake, the main dietary source of long chain omega‐3 fatty acids, on asthma in children. Results: A total of 1119 publications were identified. Twenty‐three studies on fish intake in association with childhood asthma were included in the final review. In 15 of 23 studies, early introduction of fish (6‐9 months) and regular consumption (at least once a week) improved asthma symptoms and reduced risk in children 0‐14 years as compared to no fish consumption; 6 of 23 showed no effect and 2 of 23 studies suggest adverse effects. Meta‐analysis revealed an overall "beneficial effect" for "all fish" intake on "current asthma" [OR: 0.75; 95%CI: 0.60‐0.95] and "current wheeze" [OR: 0.62; 95%CI: 0.48‐0.80] in children up to 4.5 years old. An overall protective effect of "fatty fish" intake as compared to "no fish" intake in children 8‐14 years old was also observed [OR: 0.35; 95%CI: 0.18‐0.67]. Conclusion: This meta‐analysis suggests that introduction of fish early in life (6‐9 months) and regular consumption of all fish (at least once a week) reduces asthma and wheeze in children up to 4.5 years old, while fatty fish intake may be beneficial in older children. Future well‐designed clinical trials are recommended to confirm the promising findings documented in this literature analysis.